EXTRACTION OF PHENOLIC COMPOUNDS FROM PETAI LEAVES (PARKIA SPECIOSA HASSK.) USING MICROWAVE AND ULTRASOUND ASSISTED METHODS - Buanasari, Buanasari; Eden, Willy Tirza; Sholichah, Ayu Ina (Jurnal Bahan Alam Terbarukan, 2017)
The antioxidant has an activity to neutralize free radical compound that the body needs to avoid damage cells and tissues. Phenolic is one of the compounds that have an antioxidant activity. The influences of ultrasonic-assisted extraction (UAE) and microwave-assisted extraction (MAE) conditions on phenolic compounds of Parkia speciosa Hassk. leaves were investigated. The effects of temperature (40°C, 50°C, 60°C and 70°C), time (10, 30 and 50 minutes) and material-solvent ratio (1:10, 1:13, 1:15 ) were evaluated based on the yield, total phenolic content (TPC) and antioxidant activity. The result showed that the highest yield (15.82%) was obtained at 1:15 (w/w) of material-solvent ratio, 50°C of temperature and 50 minutes of extraction time for MAE. The highest yield of UAE is 15.53% that sample was obtained at 1:13 (w/w) of material-solvent ratio, 60°C of optimal temperature and 30 minutes extraction time. The highest IC50 of UAE method extract was 52.55 ppm, while the extract obtained using MAE method was 50.44 ppm. UAE is more stable at higher temperatures. Time and solvent which was used more efficient than MAE. Extract of petai leaves (Parkia speciosa Hassk.) were very potential to be used as a source of natural antioxidants because they have IC50 values from 41.39 to 66.00 ppm. Its antioxidants capacity is ranged from strong to very strong capacity.